2023
DOI: 10.3390/plants12233963
|View full text |Cite
|
Sign up to set email alerts
|

A Travel through Landscapes of Seed Dormancy

Alberto Gianinetti

Abstract: Basic features of seed dormancy are illustrated. The seed overall regulatory network governs seed metabolism and development, and it is coordinated by plant hormones. A functional model focused on abscisic acid (ABA), the foremost plant hormone in dormancy, is used as a framework to critically discuss the literature. Gibberellins (GAs) have a main role in germination, and the ABA–GAs balance is a typical feature of the seed state: ABA dominates during dormancy and GAs prevail through germination. Thus, the lit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 200 publications
0
3
0
Order By: Relevance
“…For seeds with physiological dormancy, the balance between their endogenous ABA and GA 3 contents can be regulated to break seed dormancy [45]. Gibberellin is effective in lifting the physiological dormancy of seeds and promoting seed germination [46]. In this study, it was found that low-temperature treatment combined with gibberellin (300 mg/L) could promote seed germination more effectively.…”
Section: Seed Dormancy Releasementioning
confidence: 75%
See 1 more Smart Citation
“…For seeds with physiological dormancy, the balance between their endogenous ABA and GA 3 contents can be regulated to break seed dormancy [45]. Gibberellin is effective in lifting the physiological dormancy of seeds and promoting seed germination [46]. In this study, it was found that low-temperature treatment combined with gibberellin (300 mg/L) could promote seed germination more effectively.…”
Section: Seed Dormancy Releasementioning
confidence: 75%
“…The germination of Chinese olive seeds after a short period of cold stratification or gibberellin treatment suggests that olive seeds have non-deep physiological dormancy. In contrast, seeds with deep physiological dormancy are not affected by gibberellin treatments and usually require more than 3 months of cold stratification to promote germination [4,46].…”
Section: Seed Dormancy Releasementioning
confidence: 99%
“…Seed dormancy can be relieved with storage time of dry seeds, and can be reversed by stratification of the imbibed seeds at any time point (Bewley et al 2013). ABA is the primary hormone in maintenance of dormancy, and gibberellins (GA) are the key players in germination (Gianinetti 2023). Thus, the ABA to GA ratio determines the fate of germination.…”
Section: Resultsmentioning
confidence: 99%